Acceptance of Nanotechnology Among Halal Food Manufacturer - Siti Norbilah, Abdul Manaff (2012)
In today’s competitive market technology, it is essential to keep leadership in the food and food processing industry. Consumers demand fresh authentic, convenient and flavourful food products. The future belongs to new products and new processes, with the goal of enhancing the performance of the product, prolonging the product shelf life and freshness, and improving the safety and quality of food. Nanotechnology is an enabling technology that has the potential to revolutionise the food industry. The objective of this research is to identify the identify the factors that contribute to the readiness of the halal food company to participate in nanotechnology. Base on the theoretical framework, the independents variable are benefits,complexity, compatibility and environment and the dependent variable is the Nanotechnology in Halal Food Readiness. The data was gather from the questionnaire session and also from journals, books, newspaper, articles and also through internet. The data collected were analyzed using SPSS. As a result, the independence variable Complexity and Environment influences the Nanotechnology in Halal Food Readiness and the benefit and compatibility are not supported the nanotechnology in halal food readiness. For the conclusion, the halal food company should gain more knowledge about new technologies called nanotechnologies for the better result on producing the halal food.